2022
DOI: 10.1007/s00289-022-04461-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel antiviral nanofinishes for bioactive textiles

Abstract: Virus-caused public health outbreaks represent a serious threat to humans all over the world. The rampant new 2019 coronavirus (SARS-CoV-2) has wreaked havoc on China and the rest of the world since December 2019. Now focus is on effective reduction of corona and other viral and bacterial infections in hospitals, public and private sectors, households, schools, etc. Metal and metal oxide nanoparticles, carbon nanotubes, heterostructures, patterned surfaces, and graphene-based materials have shown up to 99.9998… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, the application of chloroxylenol as an antimicrobial agent for the finishing of textiles to develop bioactive textiles has not yet been explored. 11 According to current state-of-the-art knowledge, existing bioactive agents have been applied to textiles using crosslinkers, 12 binders, 13 and coupling agents, 14,15 and the maximum washing durability of such finished bioactive textiles is up to 20 rounds of domestic laundry. Because of their poor washing durability, the applied biocides continuously leached from the fabric into the drain during each wash cycle, which had a detrimental effect on the microbes present in the sewage that were necessary for sewage biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the application of chloroxylenol as an antimicrobial agent for the finishing of textiles to develop bioactive textiles has not yet been explored. 11 According to current state-of-the-art knowledge, existing bioactive agents have been applied to textiles using crosslinkers, 12 binders, 13 and coupling agents, 14,15 and the maximum washing durability of such finished bioactive textiles is up to 20 rounds of domestic laundry. Because of their poor washing durability, the applied biocides continuously leached from the fabric into the drain during each wash cycle, which had a detrimental effect on the microbes present in the sewage that were necessary for sewage biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to copper, also other compounds have been used to create antiviral textiles. ZnO films have been used to coat nanofibrous electrospun silk-polyethylene oxide material for antiviral purposes [ 12 ] and ZnO nanoparticles coupled with (3-Glycidoxypropyl) trimethoxysilane have been used to create antiviral cotton fabric [ 13 ]. Selenium nanoparticles as part of acrylate-based printing paste have been used to print antiviral polyester fabrics [ 14 ] and nano-graphene oxide coating was used in two studies that aimed to prepare antiviral PET textile and linen [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…CuI nanoparticles treated textiles decreased the infectivity of SARS-CoV-2 only up to 2.5 logs during 24 h incubation [ 11 ], Cu-impregnated cotton decreased the infectious titer of influenza A virus by ≥ 2 log during 30 min and other type of Cu-coated textile exhibited only a maximum of 1–2 log decrease in infectivity of vaccinia virus, herpes simplex virus type 1 and influenza A virus H1N1 during 2 h [ 9 ]. Most of other nanomaterial-based textiles involving either ZnO, selenium or graphene oxide surface coatings, have shown antiviral activity between 1 and 2 log decrease of infectious units during 1–2 h [ [12] , [13] , [14] , 16 ]. In terms of the duration of exposure, the shortest contact time during which significant (1.5 log) decrease of viral infectivity was observed was 1 min in case of liquid soap treated face masks [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their advantage is the selective toxicity to bacteria and minimal effect on human cells [ 20 , 21 ]. Recently, the investigation has been focused on the antiviral efficiency of ZnO nanoparticles, and it has been established that their presence is responsible for viral load decreases [ 22 , 23 ]. Jana et al found that the incorporation of the in situ synthesized ZnO particles into a polymer structure of chitosan or into phenyloxy-functionalized chitosan improved their stability and effective antiviral activity toward human cytomegalovirus [ 24 ].…”
Section: Introductionmentioning
confidence: 99%